Role Space, Organizational Commitment and Perception about the Organization among Retail/Sales Professionals in Saudi Arabia - Azeem Syed Mohammad (SEISENSE Journal of Management, 2018)
This study examines the relationship between role space and organizational commitment among the sales professionals in the Kingdom of Saudi Arabia. Moreover, the study also examines the relationship between organizational commitment and employee perception about the organization they work for. The data were obtained from 148 sales and retail professionals. The gathered data were then analyzed by using suitable statistical tools. The results demonstrate that role space is significantly and negatively related to overall commitment among the selected respondents. Employee perception of the organization is found significantly positively related to affective commitment, normative commitment, and overall commitment. Regression analysis indicates that the change in overall OC is explained by 43.5% resulting from a change in the selected independent variables.